Application of new technologies for increasing fatigue characteristics of lock-on connec¬tions of compressor blades - Леховицер, В. А.; Мозговой, В. Ф.; Липский, Е. Р.; Балушок, К. Б. (Proceedings of National Aviation University (archive), 1999)
Considered are new technologies of high-speed prototyping aimed at receiving physical dublicate of special computer model of a machine part